(untitled) (Prostor, 2023)
In an attempt to revisit two architectural pieces of commemoration designed by two influential architects, the Garden of Exile by Daniel Libeskind and the Memorial for the Murdered Jews of Europe by Peter Eisenman, it is worthwhile to recall Sigmund Freud’s 1925 essay “A Note Upon the ‘Mystic Writing-Pad”. This paper elaborates on the association between writing and memory and introduces how these architects use topography while placing gigantic rectangular blocks as a peculiar analogy to Freud’s technique per se, that is, ‘writing on a surface.’ This argument opens up the discussion on the longitudinal cross sections and the experiential qualities of these projects concentrating on their particular internalization of memory and time. Then comes Walter Benjamin and his notion of allegory into the picture to claim that Libeskind’s concept of ‘reading the note’ may differ from Eisenman’s in a reasonably crucial way. The latter’s architecture expands the idea of memory and it’s further functioning and places it in the realm of allegorical experience.